2017
DOI: 10.29252/ijrm.15.2.75
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of gonorrheal and chlamydial infections in Zanjanian women in 2013-2014

Abstract: Background: Chlamydia trachomatis and Neisseria gonorrhoeae are the most prevalent bacterial sexually transmitted diseases in women.Objective:The purpose of this study was to investigate the prevalence of gonorrheal and chlamydial infections and determination of related risk factors in married women with vaginal discharge attending gynecological outpatient department (OPD) in Zanjan in 2013-2014.Materials and Methods: In this cross sectional study, 100 married women aged 18-49 years with vaginal discharge were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…The result of the current study showed that 6% of symptomatic married woman were declared as positive of Neisseria gonorrhoeae on the basis of microbiological evaluation supported by molecular characterization of orfi gene. Our results are partially in agreement with Molaei who reported that 4% of married gonorrhoeae suspected patients were confirmed through bacterial culture and serological test [18] . In the current study 3% of un married asymptomatic women were declared as positive of Neisseria gonorrhoeae by molecular characterization of orf1 gene.…”
Section: Discussionsupporting
confidence: 93%
“…The result of the current study showed that 6% of symptomatic married woman were declared as positive of Neisseria gonorrhoeae on the basis of microbiological evaluation supported by molecular characterization of orfi gene. Our results are partially in agreement with Molaei who reported that 4% of married gonorrhoeae suspected patients were confirmed through bacterial culture and serological test [18] . In the current study 3% of un married asymptomatic women were declared as positive of Neisseria gonorrhoeae by molecular characterization of orf1 gene.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of Chlamydia infection was found 18% in cases which is in good agreement with two previous studies from Iran and Europe. They also showed that frequency of CT were 16% and 13.4% in Iranian 24 and European populations 25 respectively. Besides, there is also another study which found higher prevalence of CT in symptomatic women i.e.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, other studies from Iran reported more close prevalence rate for N. gonorrhoeae to the current study's results. For instance, the prevalence of N. gonorrhoeae was respectively 4.0%, 5.6%, and 4.10% in Zanjan, Fars, and Qom provinces [10,16,17]. It seems that the prevalence of N. gonorrhoeae in Ilam province is approximately similar to other provinces in Iran.…”
Section: N Discussionmentioning
confidence: 97%